The Stunting Awareness Community Movement in Suka Maju, Jambi Luar Kota, Muaro Jambi - Neni Heryani; Ruwayda Ruwayda; Murdayah Murdayah (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
The Stunting Awareness Community Movement is a program that aims to encourage a culture of healthy living and increase knowledge and understanding of stunting through interventions, education, and exploration of and growth in people's creativity to prevent stunting through the processing of nourishing food based on local food resources, leaving unhealthy habits and behavior of society. Outreach and training for up to 45 gemasting cadres with a pretest and posttest constitute community service. The findings of the pre-test values for cadres show that, on average, they were unaware of the precise signs of stunting, as well as the special therapies and diets that could prevent child stunting. The post-test result reveals that the lowest score was 9 the highest was 15 and that the cadres' average knowledge score was 13,70 The right response is known to the typical cadre. When the distribution of the data was not normal, a Wilcoxon test was used to measure knowledge before and after the data normality test. The test's value of 0,000 indicates that training had an impact on cadres' understanding of reducing toddler stunting. The output goals include establishing gemasting cadres and improving partner communities' knowledge, comprehension, perceptions, and abilities to reduce stunting.